High Performance Spring Programming - Myalapalli, V.K (International Journal of Computer Sciences and Engineering, 2014)
In the contemporary world Spring Application Framework is the most prevalently used application framework due to its IoC (Inversion of Control) property. Many of the Spring developers simply do programming with less concern towards optimized processing. Though Spring Framework offers sundry ways of programming techniques to reach the same end, certain practices are pre requisite to ensure that consequences will be prolific. This paper proposes miscellaneous, simple, reliable, flexible and easy techniques to make programs more efficient. The exploration in this paper would serve as a benchmarking tool for assessing best programming practices. Experimental results of analysis designate that maintainability, flexibility and reusability are enhanced.